Frontispiece: Snapshots of Dynamic Adaptation: Two‐Dimensional Molecular Architectonics with Linear Bis‐Hydroxamic Acid Modules. Issue 52 (17th December 2019) - Jing, Chao; Zhang, Bodong; Synkule, Sabine; Ebrahimi, Maryam; Riss, Alexander; Auwärter, Willi; Jiang, Li; Médard, Guillaume; Reichert, Joachim; Barth, Johannes V.; Papageorgiou, Anthoula C.
Abstract : 2D Nanostructures In their Research Article on page 18813, J. Reichert, J. V. Barth, A. C. Papageorgiou et al. present complex 2D networks featuring chiral pores that originate from the progressive deprotonation of an adsorbate on Ag(111).